MOTIVACIJA ZAPOSLENIH I OBUKA MENADŽERA TOKOM PANDEMIJE COVID-19 - Stankovic, Tanja; Radojević, Tijana (The European Journal of Applied Economics, 2022)
Company survival depends on its ability to adapt to the changes that have their own pace and dynamics of development, it is the transition from the present to the future, desired state. The activities of the organization’s management could lose the meaning if there is lack of motivation. In situation like this, implementation cannot be successful. Employee motivation factors for work, advancement and organizational change are numerous, but the most important is the communication between employees and management. As this communication is closely related to management coaching, manager’s coaching skills become crucial for the motivation and ultimate success of the organization. This research aims to show the importance of motivating employees to learn and improve skills during work and identify the best individuals who can become internal trainers who will transfer their knowledge to employees.